Comparison of the Fatty Acid and Triglyceride Profiles of Big Eye Tuna (Thunnus obesus), Atlantic salmon (Salmo salar) and Bighead Carp (Aristichthysnobilis) Heads - Jing Zhang (Molecules, 2019)
Big eye tuna (Thunnus obesus), Atlantic salmon (Salmo salar) and bighead carp (Aristichthys nobilis) are three representative marine and fresh water fishes. In this study, the content of total lipids (TL), triglyceride (TG) fraction, and the fatty acid profiles in the corresponding fish heads were analyzed. Meanwhile, their complicated TG molecular species were further characterized. The results showed that TG was the major lipid in these three fish heads (60.58−86.69%). Compared with other two fish heads, big eye tuna head was the most abundant in polyunsaturated fatty acids, among which eicosapentaenoic acid (EPA) + docosahexaenoic acid (DHA) accounted for 64.29% and 32.77% in the TL and TG fraction, respectively. It is also worth noting that EPA+DHA/total fatty acid (TFA) value of TL and TG fraction from bighead carp head showed no significant difference with Atlantic salmon head, a typical marine fish. There were 146 TG molecules detected in big eye tuna head, 90 in Atlantic salmon and 87 in bighead carp heads. DHA or EPA accounted for 56.12%, 22.88%, and 5.46% of the total TG molecules in these three fish heads, respectively. According to principal component analysis, orthogonal projection to latent structures-discriminant analysis and the constructed heat map, the three samples could be completely differentiated based on their TG molecule fingerprints. This study is the first to compare marine and fresh water fish from the perspective of their heads’ fatty acid and TG molecule profiles.